2004
DOI: 10.1023/b:mcbi.0000041856.92497.0c
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes decreases mRNA levels of calcium-release channels in human atrial appendage

Abstract: Patients with chronic diabetes mellitus usually develop reductions in rate and force of cardiac contractions. Since calcium-release channels (ryanodine receptors (RyRs) and inositol 1,4,5-trisphosphate receptors (IP(3)Rs)) play integral roles in effecting these processes, we rationalize that alterations in their expression may underlie these defects. To test this hypothesis, right atrial appendages were obtained from diabetic (65.0 +/- 4.5 years) and nondiabetic (56.2 +/- 2.6 years) patients undergoing coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
3
13
0
Order By: Relevance
“…One of these proteins is RyR2, the channel through which calcium ions leave the sarcoplasmic reticulum to trigger cardiac contraction. We and others have shown that expression of this protein decreases in hearts of chronic diabetic patients (8,9). Using the STZ-induced diabetic rat model, we have also shown that in addition to a decrease in expression, the functional integrity of RyR2 decreases with diabetes (14,15,19).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…One of these proteins is RyR2, the channel through which calcium ions leave the sarcoplasmic reticulum to trigger cardiac contraction. We and others have shown that expression of this protein decreases in hearts of chronic diabetic patients (8,9). Using the STZ-induced diabetic rat model, we have also shown that in addition to a decrease in expression, the functional integrity of RyR2 decreases with diabetes (14,15,19).…”
Section: Discussionsupporting
confidence: 52%
“…We and others have shown that expression of this protein decreases in hearts of chronic diabetic patients (8,9) as well as in the streptozotocin (STZ)-induced diabetic rats (10 -13). Using the latter model, we found that in addition to a decrease in expression of RyR2, its functional integrity is also compromised in diabetes (14,15).…”
mentioning
confidence: 99%
“…As a consequence, SR Ca 2+ load is reduced, and SR Ca 2+ release and re-uptake are impaired [181,182]. Interestingly, an increased [184,185]. Both increased and decreased IP 3 production in response to α-adrenergic stimulation has been reported in diabetes [186,187].…”
Section: Diabetic Cardiomyopathymentioning
confidence: 99%
“…Interestingly, an increased propensity toward arrhythmogenic afterdepolarizations has been observed in diabetic cardiomyocytes [182]. Insulin increases IP 3 concentration and triggers arrhythmic Ca 2+ release events in myocytes from diabetic ob/ob mice -but not from wild-type mice -and this effect is mediated via IP 3 signaling [183].IP 3 R expression (type 1 and type 2 IP 3 Rs) is unaltered in ventricles from ob/ob mice [183], but decreased in a diabetes model in the rat and in atrium from diabetic patients [184,185]. Both increased and decreased IP 3 production in response to α-adrenergic stimulation has been reported in diabetes [186,187].…”
Section: Diabetic Cardiomyopathymentioning
confidence: 99%
“…RNA samples were used as templates for synthesis of firststrand cDNAs as previously described (10). Briefly, 1 l of oligo dT15 primer (Promega) was added to equivalent amounts of total RNA obtained from coronary arteries isolated from control (n ϭ 4) and high-fat diet dogs (n ϭ 4).…”
Section: Thismentioning
confidence: 99%